Legal Functions in the Community as Tools to Change Behavior (Legal Function Assessment from The Sociology of Law Perspective) - Sarjiyati (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The sociology of law is a science that theoretically analyzes and empirically highlights the effect of social phenomena on the law, and vice versa. The law by positivistists is seen as texts and eliminates human role factors, gets a great correction by placing the human role in a less central position. Legal sociology finds that the role of human behavior is much more varied. The law as behavior arises instantly through the interaction between the members of society itself. Social and legal change or otherwise do not always go together. Because in certain circumstances the development of law may be left behind by the development of other elements of society and its culture. Law has a function as a means of social control, as a means of social engineering and integration. The important function of the rule of law is as guiding behavior. So any rule of law will have an impact on human behavior. The impact is what is called a response to a legal provision. The response is different from every human, there are positive and negative responses. So the impact of the provisions of the law, not just obedience but there is a form of disobedience.